2021
DOI: 10.1016/j.bbrc.2021.03.141
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of farnesyltransferase inhibitor on sepsis-induced morphological aberrations of mitochondria in muscle and increased circulating mitochondrial DNA levels in mice

Abstract: Sepsis remains a leading cause of mortality in critically ill patients and is characterized by multi-organ dysfunction. Mitochondrial damage has been proposed to be involved in the pathophysiology of sepsis. In addition to metabolic impairments resulting from mitochondrial dysfunction, mitochondrial DNA (mtDNA) causes systemic inflammation as a damage-associated molecular pattern when it is released to the circulation. Metabolic derangements in skeletal muscle are a major complication of sepsis and negatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…CoQ10 deficiency causes mitochondrial dysfunction. Increased circulating mtDNA levels are considered to be associated with mitochondrial disintegrity [ 60 , 61 ] as well as with cellular damage. Therefore, we measured plasma mtDNA levels as a biomarker that reflects mitochondrial dysfunction/disintegrity as well as systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…CoQ10 deficiency causes mitochondrial dysfunction. Increased circulating mtDNA levels are considered to be associated with mitochondrial disintegrity [ 60 , 61 ] as well as with cellular damage. Therefore, we measured plasma mtDNA levels as a biomarker that reflects mitochondrial dysfunction/disintegrity as well as systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, not only a diminished number of mitochondria, but also ultrastructural changes in the remaining organelles point to severe alterations in mitochondrial integrity during critical illness. Mitochondrial swelling, a fragmented or nearly absent cristae structure, matrix space enlargement and vacuolization are the most frequent morphological pathologies that have been reported in animal [ 79 , 80 , 103 ] and human [ 13 , 104 ] skeletal muscle biopsies associated with critical illness-induced muscle wasting. In accordance with the rapid development of muscle weakness and the degradation of muscle mass due to critical illness, the decrease in mitochondrial content can be observed within several days after ICU admission [ 83 ].…”
Section: Structural and Functional Impairments Of Mitochondria In Icu...mentioning
confidence: 99%
“…So far, studies have demonstrated that mitochondrial dysfunction plays an important role in the pathogenesis of sepsis [ 3 , 4 , 5 , 6 ]. Mitochondria, the organelles that produce the energy required by human body, play a key role in the whole life activities of human body.…”
Section: Introductionmentioning
confidence: 99%